2019
DOI: 10.1002/ar.24325
|View full text |Cite
|
Sign up to set email alerts
|

Variation in accessory mental foramen frequency and number in extant hominoids

Abstract: Nerves providing sensation to the lower face and jaw exit the mandibular canal via the mental foramen. In humans, there are many documented occurrences of additional foramina (accessory mental foramina, AMFs) on the lateral mandibular surface that may also contain nervous structures. There are large discrepancies in the literature regarding how often AMFs occur in humans, and investigations of non-human hominoid AMFs are rare. Consequently, the causes of interspecific diversity in this variable have not been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 64 publications
(174 reference statements)
1
8
0
Order By: Relevance
“…Although no quantitative analyses were performed on the number of mental foramina in the dataset here, all specimens in this sample had between one and nine mental foramina. This was consistent with prior literature (e.g., Robinson & Yoakum, 2019), in that the larger specimens did have more accessory mental foramina (AMF) than smaller specimens, except for S. sciureus. Many of the S. sciureus specimens had between 3-4 AMFs.…”
Section: Mandibular Canal Variationsupporting
confidence: 92%
See 1 more Smart Citation
“…Although no quantitative analyses were performed on the number of mental foramina in the dataset here, all specimens in this sample had between one and nine mental foramina. This was consistent with prior literature (e.g., Robinson & Yoakum, 2019), in that the larger specimens did have more accessory mental foramina (AMF) than smaller specimens, except for S. sciureus. Many of the S. sciureus specimens had between 3-4 AMFs.…”
Section: Mandibular Canal Variationsupporting
confidence: 92%
“…While little research has focused on variation in the mandibular foramen in mammals other than humans, a significant body of research exists on the mental foramen with a particular emphasis on factors that affect its placement, size, and number. Although earlier studies (e.g., Olivier, 1927, 1928; Starkie & Stewart, 1931) argued that the mental foramen was uniform across humans in its placement and size, more recent studies focusing on factors such as growth and development (Anderson et al, 1991; El‐Beheri, 1985; Williams & Krovitz, 2004), differences in feeding behaviors and side preference during mastication (Agarwal & Gupta, 2011; Amorim et al, 2008; Voljevica et al, 2015; Yesilyurt et al, 2008), diet (Moore et al, 1968), age (Charalampakis et al, 2017; Gabriel, 1958; Gershenson et al, 1986; Heasman, 1984; Iwanaga et al, 2019; Wadu et al, 1997; Xie et al, 1997), and number of mental foramina (Kramer, 1989; Montagu, 1954; Riesenfeld, 1956; Robinson & Yoakum, 2019; Simonton, 1923) have shown that there is substantial variation within humans and some non‐human primates. However, there is no consensus as to which of these factors, if any, play a significant role in the size, shape, and number of the mental foramen in primates.…”
Section: Introductionmentioning
confidence: 99%
“…3 Before this stage, when the ramification of the mental nerve has occurred, an accessory foramen can exist according to the principle of the bone response to the changes in nervous tissue formation. 24 The rate of accessory MF reported 2%-55.5% in range using different methods and in various populations. 6,8,10,11,20,25 The lower prevalence of the accessory MF was reported in white Americans (1.4%) and Asians (1.5%).…”
Section: Studymentioning
confidence: 98%
“…The mandibular canal (MC) is located within the mandible and hosts the inferior alveolar nerve and artery: it opens posteriorly through the mandibular foramen and anteriorly through the mental foramen (MF) [1]. The inferior alveolar nerve divides into its two branches-respectively, the incisive nerve and the mental nerve: the latter one passes through the MF together with the mental artery [2][3][4]. The MF represents a crucial anatomical point, as the mental nerve can be injured in several dental procedures, including endodontic procedures, overfilling, teeth extractions and implantology [1], with consequent sensory alterations of the inferior facial third medially to the MF [5].…”
Section: Introductionmentioning
confidence: 99%